Clinical profile and excellent short-term treatment outcome of acute glomerulonephritis: a report from paediatric nephrology unit of university teaching hospital, Uyo, Nigeria - Dixonumo, Ofonime T.; Ikpeme, Enobong E.; Kan, Kate M. (International Journal of Research in Medical Sciences, 2020)
Background: Acute glomerulonephritis (AGN), the commonest of which is acute post streptococcal glomerulonephritis, is common in school aged children and typically presents with haematuria, oedema, oliguria and varying degrees of renal insufficiency. This study evaluated epidemiologic factors, presentations and treatment outcome of AGN patients at University of Uyo Teaching Hospital, (UUTH), Uyo, Nigeria. Methods: This cross-sectional study was conducted among children with AGN at the paediatric nephrology unit of UUTH from January 2015 to December 2019. Data were analysed with statistical package for social sciences version 25 and p values <0.05 were considered statistical significant. Results: Fifteen out of 12,403 paediatric admissions had AGN, giving an average yearly hospital incidence of 3/year and 0.12% of total admission. Age range was three to 15 years. Mean age was 8.07±3.94 years and median was 7.00 years. Males were nine with a male/female ratio of 1.5:1. Eight (53.3%) belonged to the lowest socioeconomic class. Haematuria and peripheral oedema were universal presentations and 4 (26.7%) had antecedent pharyngeal infection. Other clinical presentations were: Oliguria 11(73.3%), Grade II hypertension 10 (66.7%), and pulmonary oedema 5 (33.3%). Four (26.7%) each had acute kidney injury, hyperkalaemia and dipstick massive proteinuria. Other complications were congestive cardiac failure 2 (13.3%), and seizures with encephalopathy in 1 (6.7%). Proteinuria was significantly associated with age at p=0.034 (Fisher Exact test). Major treatment modalities were: fluid management, loop diuretics and antibiotics as indicated. Conclusions: Short-term outcome was excellent with 100% discharge within 28 days of hospitalisation and the majority being discharged within two weeks.